Figuring Code-switching and Code-mixing Use in the Movie â€œAli & Ratu-Ratu Queensâ€ - Sarifah Achmad; Inggil Azkarahma; Sulis Adita Permana; Silmy Ashyya (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This study aims to figure out the utterances using code-switching and code-mixing in the movie Ali & Ratu-Ratu Queens and determine the types code switching and code mixing found between Indonesian and English. The analysis of code-switching is based on Poplackâ€™s theory in Romaine (1995) while to investigate the use of code-mixing by Muyskenâ€™s (2000) theory on this particular issue is implemented. An observation method was conducted to gain a comprehensive understanding of the context and note-taking the findings before classifying the findings into tables to ease comprehension of the readers. The study revealed the most frequent use type of code-switching is tag-switching While the most frequent used type of code-mixing is insertion code-mixing Further study is wished to gain deep understanding on the function and the meaning behind the use of those code-switching and code-mixing utterances in the movie.Â Figuring Code-switching and Code-mixing Use in the Movie â€œAli & Ratu-Ratu Queensâ€